Poly-β-(1→6)-N-acetyl-D-glucosamine mediates surface attachment, biofilm formation, and biocide resistance in Cutibacterium acnes - Kaplan, Jeffrey B.; Cywes-Bentley, Colette; Pier, Gerald B.; Yakandawala, Nandadeva; Sailer, Miloslav; Edwards, Marc S.; Kridin, Khalaf (Frontiers in Microbiology, 2024)
Background The commensal skin bacterium Cutibacterium acnes plays a role in the pathogenesis of acne vulgaris and also causes opportunistic infections of implanted medical devices due to its ability to form biofilms on biomaterial surfaces. Poly-β-(1→6)-N-acetyl-D-glucosamine (PNAG) is an extracellular polysaccharide that mediates biofilm formation and biocide resistance in a wide range of bacterial pathogens. The objective of this study was to determine whether C. acnes produces PNAG, and whether PNAG contributes to C. acnes biofilm formation and biocide resistance in vitro. Methods PNAG was detected on the surface of C. acnes cells by fluorescence confocal microscopy using the antigen-specific human IgG1 monoclonal antibody F598. PNAG was detected in C. acnes biofilms by measuring the ability of the PNAG-specific glycosidase dispersin B to inhibit biofilm formation and sensitize biofilms to biocide killing. Results Monoclonal antibody F598 bound to the surface of C. acnes cells. Dispersin B inhibited attachment of C. acnes cells to polystyrene rods, inhibited biofilm formation by C. acnes in glass and polypropylene tubes, and sensitized C. acnes biofilms to killing by benzoyl peroxide and tetracycline. Conclusion C. acnes produces PNAG, and PNAG contributes to C. acnes biofilm formation and biocide resistance in vitro. PNAG may play a role in C. acnes skin colonization, biocide resistance, and virulence in vivo.